An electricity generator model by the water delivery system of sanitary ware - Panthong, S.; Poomjan, S.; Taengtang, T.; Srinuanjan, K. (My University, 2014)
In this research is presented electricity production of sanitary ware, which can be covered kinetic energy of water to electric current from water delivery system. A small electric generator will be set on the water delivery system of sanitariums. It consists with a turbine electric generator and a big tank which build in on tank of a sanitarium. Turbine generator is generated small electric currents by a lot of water inside pipe. If this system were set in a large building for example such as department store, etc. the electric currents would be on generating in order to cumulative energy. In which Bangkok has a population about ten millions of people which sanitariums are used about a hundred millions of time per day. The experimental results of this model can be calculated electric currents to compare with systems which were set on large building. © (2014) Trans Tech Publications, Switzerland.
Keywords: Electricity; Sanitary ware; Turbine generator